Gastrointestinal Transport : Molecular Physiology - Barrett, Kim E.; Donowitz, Mark, 1943- (Current topics in membranes, 2001)
This title contains comprehensive reviews of novel information in intestinal transport, including control of nutrition in gene regulation. There are diagrammatic representations of key concepts and processes. Additionally, this volume offers new insight at a molecular level into the basis of intestinal disease. The topics covered in this book also relate to other epithelial organs such as the lungs, kidney, and biliary system.